A Comparative Analysis of Economic Farming Activity of Farmers Rice-Livestock Integrated Farming System (RLIFS) and Non RLIFS - Lindawati, L; Buhari Sibuea, Mhd.; Novita, Desi; Ilham Riyadh, Muhammad; Hasibuan, Abdurrozzaq (International Journal of Engineering and Technology, 2018)
Integrated farming system is a system that emphasized linkages and synergism of farming units waste utilization. The objective of this study was to analyzeÂ the economic farming activity of Rice Livestock Integrated Farming System (RLIFS) and non RLIFS farmers. The results showed the usage allocation of family and external labor to RLIFS farmers was relatively greater than non RLIFS farmers. The RLIFS farmersâ€™ income of rice farming, other crops and non-agricultural was relatively larger than non RLIFSÂ farmers, while non RLIFS farmers had greater income from livestock (cow and non cow) business and farm labor. The production costs of rice farming and livestock business were still greater in RLIFS farmers although they used manure produced by their own and also provide straw of rice production as animal feed. This was due to several factors (1) The proportion of the cost of using manure was very small in the cost of rice farming if the use of manure only a supporting fertilizer and not the main fertilizer for plant. (2) Some farmers were still buying and using anorganic or chemical fertilizers because of their mindset who wanted fast and instantaneous ones. Some farmers also felt that manure contained less nutrients so they used it in small quantities. The household income total of RLIFS farmers was higher than non RLIFS farmers.Â Â